2013
DOI: 10.1186/1472-6963-13-157
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with reported service use for mental health problems by residents of rural and remote communities: cross-sectional findings from a baseline survey

Abstract: BackgroundThe patterns of health service use by rural and remote residents are poorly understood and under-represented in national surveys. This paper examines professional and non-professional service use for mental health problems in rural and remote communities in Australia.MethodsA stratified random sample of adults was drawn from non-metropolitan regions of New South Wales, Australia as part of a longitudinal population-based cohort. One-quarter (27.7%) of the respondents were from remote or very remote r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 51 publications
6
62
1
Order By: Relevance
“…The Obsessive Hope Report (Mendoza et al, 2013) identified people diagnosed with mental illness living in rural and regional areas as among the most vulnerable. This view is supported elsewhere with evidence of higher prevalence of significant mental health issues (Hauenstein, 2008;Perkins et al, 2013), less access to services than metropolitan areas, greater costs (Health Workforce Australia, 2013), and low rates of satisfaction when services are accessed (Hauenstein, 2008;Perkins et al, 2013).…”
mentioning
confidence: 85%
“…The Obsessive Hope Report (Mendoza et al, 2013) identified people diagnosed with mental illness living in rural and regional areas as among the most vulnerable. This view is supported elsewhere with evidence of higher prevalence of significant mental health issues (Hauenstein, 2008;Perkins et al, 2013), less access to services than metropolitan areas, greater costs (Health Workforce Australia, 2013), and low rates of satisfaction when services are accessed (Hauenstein, 2008;Perkins et al, 2013).…”
mentioning
confidence: 85%
“…Most mines operate 24 hours, 7 days per week, and employees often work long hours (ie, 12 hours or longer shifts),13 with rosters that are both rotating (work periods that consist of both day and night shifts)13 and compressed (a high number of shifts over consecutive days). Mines are often located in isolated regions, where employees are separated from family and social support networks, and the availability of professional support services is limited 14. Consequently, employees typically face challenges such as: long working hours, shift work, geographical isolation, limited contact with families and social supports, and a highly demanding role.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, only 35% of respondents to the NSMHWB with mental disorders reported having consulted a health professional for their disorder in the 12-months prior to survey [17,18,39]. Despite being at a reputed geographical disadvantage in terms of service provision, our rural/remote participants reported higher rates of service utilisation for AD (75%) and comorbid AD+AUD (78%) over their lifetime.…”
Section: Discussionmentioning
confidence: 77%
“…Participants were selected for interview based on their level of psychological distress using Kessler 10 scores [26] in order to obtain a reasonable representation in each category of psychological distress. Interviews were offered to 100% of those with a high-range score (25+), 75% of those with a moderate-range score (16)(17)(18)(19)(20)(21)(22)(23)(24), and one-sixth of those scoring in the low range (10)(11)(12)(13)(14)(15). A total of 636 (73%) participants completed a WMH-CIDI-3.0.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation